Kyrgyz Republic : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The statistical data on the progress in transition, value-added in the main production sectors, industrial production, output of selected industrial and manufacturing products, consumer and producer prices, energy prices, average wages, labor market, export and import of goods to CIS and non-CIS countries with regard to the Kyrgyz Republic have been presented in this paper. The paper also presents the direction of trade, production, imports, and exports of energy products, external public debt, summary of state government operations, and related economic indices of the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet